Study of surface corrosion on AA 2017‐T4 aluminum alloy by using electrochemical parameters. (6th January 2016) - Abreu, C. M.; Cabeza, M.; Feijoo, I.
Abstract : In this study, we applied potentiodynamic polarization to the analysis of surface corrosion in a 2017‐T4 alloy during a stress corrosion cracking (SCC) test in 1 m NaCl solution. A constant load SCC test was chosen, classifying the applied load into three categories – no load, medium load, and high load – with the material's yield strength as a maximum load. Electrochemical measurements carried out during the SCC test allowed us, by plotting the current density versus the applied potential on a logarithmic scale, to determine the electrochemical characteristic parameters for each load category. These parameters, combined with both cross‐sectional and surface morphological analysis, were used to qualitatively characterize the corrosion of the aluminum alloy. All tests performed revealed two different attack behaviors, one characterized by shallow pits and the other by a deep, intergranular penetration. The presence of each behavior depends on the intensity of the applied load, which involves variations in the polarization curve and therefore modifies the electrochemical parameters. Copyright © 2016 John Wiley & Sons, Ltd.